Cytotoxic Activity of Fatty Acids From Antarctic Macroalgae on the Growth of Human Breast Cancer Cells - Pacheco, Bruna Silveira; dos Santos, Marco Aurélio Ziemann; Schultze, Eduarda; Martins, Rosiane Mastelari; Lund, Rafael Guerra; Seixas, Fabiana Kömmling; Colepicolo, Pio; Collares, Tiago; Paula, Favero Reisdorfer; De Pereira, Claudio Martin Pereira (Frontiers in Bioengineering and Biotechnology, 2018)
Macroalgae are a natural source of clinically relevant molecules such as polyunsaturated and monounsaturated fatty acids. The Antarctic environment, due to its cold climate, leads to high production of these bioactive molecules. Adenocystis utricularis, Curdiea racovitzae, and Georgiella confluens from three distinct islands in the Antarctic Peninsula were collected and analyzed for their fatty acid content by gas chromatography flame ionization detection. Results revealed that the algal extracts consisted of 22 fatty acids, of which 9 were saturated, 4 were monounsaturated, and 9 were polyunsaturated (PUFA). In addition, fucosterol was identified within the lipidic extracts. The cytotoxic activity of these fatty acids was evaluated in human breast cancer cell lines MCF-7 and MDA-MB-231. The most notable result was the effect of PUFA on the growth inhibition of cancer cells ranging from 61.04 to 69.78% in comparison to control cells. Significant cytotoxic activity of fatty acids from A. utricularis was observed at 48 h, resulting in an inhibition of growth of more than 50% for breast cancer cells at a concentration of 100 μg/mL. A cell viability assay showed that the fatty acids from A. utricularis significantly reduced cell viability (68.7% in MCF-7 and 89% in MDA-MB-231 after 72 h of exposure). At the same time, DAPI staining demonstrated chromatin condensation, and apoptotic bodies formed in cells that were cultured with fatty acids from A. utricularis. These data indicate that fatty acids from Antarctic macroalgae have the potential to reduce the proliferation of and induce apoptosis in breast cancer cells.